Implementation of the numerical analysis of dynamic loads on the composite structure employing the FE method - Subhi, Kussay Ahmed; Hussein, Emad Kamil; Al-Jumaili, Shaymaa Abdul Khader; Abbas, Zaid Ali (Eastern-European Journal of Enterprise Technologies, 2022)
In this research, a numerical investigation has been conducted to analyze the dynamic load of the composite structure. The composite structure was solved and analyzed using the static structure tool. There is a physical model that has been imported and meshes have been done accordingly. Shear stress, von-mises stress, and total deformation are all considered as part of the analysis. Using finite elements to simulate the composite structure and response to the applied loads. Because dynamic loads were regularly applied, frequency response was examined. In this study after verification of this computer simulation with experimental results and the results showed it was confidence 95 %. This percentage confidence allows proceeding numerical analysis. Deformation of the entire structure has been computed and found to be 10 mm, which is the maximum amount of overall deformation that can be caused by the applied load, In the Y-axis, a dynamic load was applied. The imposed dynamic load has been studied numerically and interpreted in terms of shear stresses. As a result of the maximum applied load, the maximum shear stress is 10 MPa. The complete composite construction was subjected to Von-Mises stress measurements. The structure's ability to withstand these stresses was determined by conducting a series of tests. The greatest von mises stress that can be applied in this study was 40 MPa. An investigation of how to react to vibration has already been carried out. In the numerical results, it was found that the reaction to the vibration was inconsistent. In terms of amplitude, the highest values may be found at 200 Hz, while the lowest values can be found at 20 Hz.